Prolonged persistence of a novel replication-defective HIV-1 variant in plasma of a patient on suppressive therapy. Issue 1 (December 2016) - Rassler, Samantha; Ramirez, Roberto; Khoury, Nadeen; Skowron, Gail; Sahu, Gautam
Abstract Background Cell-free residual HIV-1 virions (RVs) persist in plasma below 20–50 vRNA copies/ml in most patients on suppressive antiretroviral therapy (ART). How RVs are produced in the body during therapy is not fully clear. In this study, we have attempted to characterize these viruses of an ART-treated patient in vitro in order to gain insights into the mechanism of their production in vivo. Methods We have reconstructed almost the entire genomes of RVs as DNA forms using the patient's residual plasma vRNA by an overlapping RT-nested PCR method, and then sequence-analyzed the cloned genomes and tested them for their biological activities in vitro. Results We found that the reconstructed molecular clones of RVs lacked antiretroviral drug-resistant mutations, as well as G-to-A hypermutations. The vDNA clones, when transfected into TZM-bl cells, released HIV-p24 into the culture media at extremely low levels. This low-level virus production was found to be due to the presence of a unique mutation (GU-to-GC) in the conserved 5′-major splice donor (MSD) motif of the corresponding vRNAs. We found that the incorporation of this point mutation by itself could cause defects in the replication of a standard HIV strain (JRCSF) in vitro. However, this novel viral variant was intermittently detected at 5 of 7 time-points in the patient's plasma over a period of 39 months during therapy. Conclusions This is the first identification of a natural point mutation (GU-to-GC) in the conserved 5′-MSD motif of HIV genomic RNA. The intermittent but prolonged detection of this replication-defective HIV variant in the patient′s plasma among other viral populations strongly suggests that this variant is released from highly stable productively infected cells present in vivo during therapy. The potential implication of this observation is that the elimination of such productively infected cells that contribute to residual viremia during suppressive therapy could be an important first step towards achieving a cure for HIV.